Why is "the day of death" better than "the day of birth"? The axiology of Qoheleth in the light of the better-proverbs in Qoh 7:1-4 = Dlaczego "dzień śmierci" jest lepszy niż "dzień urodzenia"? Aksjologia Koheleta w świetle przysłów z Koh 7: 1-4 - Żelazko, Piotr (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
The article is an exegetic analysis of the passage Qoh 7:1-4 from the Book of Ecclesiastes. The excerpt challenges the absolute statement repeated many times throughout the book about the worthlessness of all things ("vanity of vanities"). Some values are recognised as "better" than others which may be the evidence of Qoh's axiology relativity.
Keywords: Hebrew Bible; Qoheleth; Ecclesiastes; Better-proverb; comparisons; Biblia Hebrajska; Kohelet; Księga Eklezjastesa; przysłowie; porównania